Analgesic effects of various extracts of the root of Abutilon indicum linn - Naveen Goyal; Sumitra Singh; Surendra K Sharma (Wolters Kluwer Medknow Publications, 2009)
Purpose : Abutilon indicum (Linn.) sweet (Malvaceae) commonly called 'Country Mallow' is a perennial plant up to 3 m in height. It is abundantly found as a weed in the sub-Himalayan tract and in the hotter parts of India. The plant is traditionally used for treatment of several diseases like bronchitis, body ache, toothache, jaundice, diabetes, fever, piles, leprosy, ulcers, cystitis, gonorrhea, diarrhea, and so on. Abutilon indicum Linn. is reported to have hepatoprotective, hypoglycemic, antimicrobial, male contraceptive, and antidiarrheal activities. The present study was done to evaluate the analgesic potential of various extracts of the root of Abutilon indicum Linn. Materials and Methods : The powdered root (900 g) was subjected to successive solvent extraction, with solvents in increasing order of polarity, namely, petroleum ether (60 - 80΀C), methanol, and ethanol, using the soxhlet apparatus for 72 hours. The marc was extracted by cold maceration for 72 hours, to obtain a water-soluble extract. The peripheral analgesic activity was studied using acetic acid-induced writhing method in Swiss albino mice (20 - 30 g), while the central analgesic activity was evaluated by the tail flick method and the tail immersion method. Results : Results indicated that all the tested extracts, except the methanol extract, exhibited significant analgesic activity in both animals' models. Petroleum ether extract showed higher analgesic activity. The activity may be related to the central mechanism or may be due to the peripheral analgesic mechanisms. Conclusion : The present study authenticates the traditional use.